Lessons Learned from the Transgenic Huntington's Disease Rats. (18th July 2012) - Vlamings, Rinske; Zeef, Dagmar H.; Janssen, Marcus L. F.; Oosterloo, Mayke; Schaper, Frederic; Jahanshahi, Ali; Temel, Yasin
Abstract : Huntington's disease (HD) is a fatal inherited disorder leading to selective neurodegeneration and neuropsychiatric symptoms. Currently, there is no treatment to slow down or to stop the disease. There is also no therapy to effectively reduce the symptoms. In the investigation of novel therapies, different animal models of Huntington's disease, varying from insects to nonhuman primates, have been created and used. Few years ago, the first transgenic rat model of HD, carrying a truncated huntingtin cDNA fragment with 51 CAG repeats under control of the native rat huntingtin promoter, was introduced. We have been using this animal model in our research and review here our experience with the behavioural, neurophysiological, and histopathological phenotype of the transgenic Huntington's disease rats with relevant literature.